Solo Mothers and Poverty: Do Policies Matter? A Comparative Case Study of Sweden and Belgium - Ann Morissens (Luxembourg Income Study (LIS), 1999)
Although the poverty rates among solo mothers vary a lot between countries there is one common feature: solo mothers perform worse in terms of financial resources compared to married or cohabiting mothers. Even in countries with low poverty rates in general, the differences in income between solo mothers and married/cohabiting mothers remain and are significant. It is interesting to ask the question why? Again referring to a cross national setting we see that poverty rates vary widely between countries and this raises the hypothesis that different factors play a role in determining solo mothers' economic well being. In this paper the main question is: What is preventing Swedish and Belgian solo mothers from poverty? Sweden and Belgium are interesting to look at for several reasons. Looking at the poverty rates for solo mothers in both countries, we see that they are low compared to many other countries. Sweden in 1992 and Belgium in 1990 had poverty rates for solo mothers of 3.8% (Hobson and Takahashi, 1997) and 8% (Bradshaw, 1996a) whereas the poverty rates for solo mothers in some other European countries were much higher: The Netherlands (20.9%)(1991) Germany (41%) (1990) United Kingdom (58%) (1990)2. Although both countries have relatively low poverty rates for solo mothers, they do not have the same type of social policies. If we take Esping-Andersen's typology of welfare regimes (1990) as a point of reference we find two different welfare regimes. Sweden is defined as a social democratic welfare state and Belgium as a conservative/corporatist welfare state. 3. One would expect the latter to be more orientated towards the male breadwinner ideology with worse outcomes for women without male breadwinner, This is apparently not the case for solo mothers in Belgium. All this makes it interesting to look at these two countries. Is public policy the main reason for the low poverty rates and how can it be explained that different policies have almost the same outcomes?
Keywords: 330; Alleinerziehende; Armut; Armutsbekämpfung; Sozialpolitik; Schweden; Belgien